From: joel de guzman (joel_at_[hidden])
Date: 2001-05-22 06:36:59
----- Original Message -----
From: "Vesa Karvonen" :
> Anyway, you are right that the above grammar is not LL(1). However, it is
> possible to transform it to LL(1) by using left factoring:
> C -> f
> C -> ( f C'
> C' -> )
> C' -> , f )
Left factoring and other tricks obfuscate the essence of the grammar.
In many cases, you'll face a brick wall, then you'll have to apply
more tricks. The simple if-then-else (dangling else problem) construct
is a simple yet prime example.
Joel de Guzman
Boost list run by bdawes at acm.org, gregod at cs.rpi.edu, cpdaniel at pacbell.net, john at johnmaddock.co.uk